Influencia del marketing en la música un análisis cross cultural. - Ramirez Cajamarca, Estefania Fabiola (My University, 2020)
This research aims to analyze the influence of marketing from the musical retrospective of genres and artists that have emerged since 1950 until today. It also seeks to define the marketing strategies applied by great artists of the music scene and how marketing has influenced music. The research is descriptive qualitative based on the documentary method. Through the bibliographic research method, the existing information is analyzed in order to carry out a comparative analysis between countries with respect to the changes that have been generated from marketing. The personal interview was applied to an expert in the area of ​​communication and the musical environment in order to evaluate their experience as part of the descriptive method, it is like that; that the semi-structured interview format is developed covering internationalization issues with respect to what the music industry was like before with respect to the present. From the Cross Cultural analysis, it is possible to define the marketing strategies present in the artists which are: naming or personal branding, content marketing, postponement marketing, innovation, aesthetics / fashion and market.
La presente investigación pretende analizar la influencia del marketing desde la retrospectiva musical de géneros y artistas que han emergido a partir del año 1950 hasta la actualidad. También se procura definir las estrategias de marketing aplicadas por grandes artistas de la escena musical y como ha influenciado el marketing en la música. La investigación es de carácter cualitativo descriptivo basándose en el método documental. Por medio del método de investigación bibliográfica se analiza la información existente con la finalidad de realizar un análisis comparativo entre países con respecto a los cambios que se han generado a partir del marketing. Se aplicó la entrevista personal a un experto en el área de comunicación y del entorno musical con el objetivo de evaluar su experiencia como parte del método descriptivo, es así; que se desarrolla el formato de entrevista semiestructurada abarcando temas de internacionalización con respecto a cómo era la industria musical antes con respecto a la actualidad. A partir del análisis Cross Cultural se logra definir las estrategias de marketing presentes en los artistas la cuales son: naming o marca personal, marketing de contenido, marketing por aplazamiento, innovación, estética/moda y mercado.
Keywords: CROSS CULTURAL ANALYSIS; MARKETING; PERSONAL BRANDING